THE SHARIAH ADVISORY COUNCIL OF SECURITIES COMMISSION MALAYSIA RESOLUTION ON MIXED COMPANIES: A JURISTIC APPRAISAL - Muhammad Hamdan Syafieq Ahmad,; Nor Faezah Ghazi Ahmad,; Wan Noor Hazlina Wan Jusoh, (Journal of Islamic, Social, Economics and Development, 2022)
Mixed companies has been a topic of discussion by Islamic scholars for centuries.Today, the issue of mixed companies is applied to Muslim’s participation in stock investmentof a company which has impermissible elements in its business. Shariah Advisory Council(SAC) of Securities Commission Malaysia (SC) has issued its resolution on this matter. Thispaper’s intent is to critically analyze, provide juristic comments and discuss the aforementionedresolution. This paper employs library research focusing on classical Shariah books and foundthat the arguments provided by the SAC of SC in its resolution are arguable due to clearevidence from Al-Quran and Sunnah and since there are other options available to avoidinvolvement of Muslim in impermissible activities especially riba and liquor. This paper hasalso provided some considerable suggestions for SAC of SC to handle this issue. One possibleway is to create a new subsidiary for the mixed company and then sells the minority interest toengage in prohibited activities to the public through an IPO. So, those minorities who want toinvest in prohibited activities can buy this newly issued share. Thus, making a clear separationbetween permissible shares and the non-permissible ones. This will help to encourage Muslimsto invest and concentrate their wealth only on permissible investments.